PENGARUH CURRENT RATIO DAN DEBT TO ASSET RATIO TERHADAP RETURN ON ASSETS (Studi Empiris Perusahaan Manufaktur Sub Sektor Makanan dan Minuman di BEI Tahun 2015-2019) - Mega Arum; Ersi Afrisah (JURNAL ILMIAH EDUNOMIKA, 2022)
This study was conducted to determine the effect of the Current Ratio and Debt To Asset Ratio on Return On Assets (Empirical Study on Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange in 2015-2019. The determination of the sample in this study used purposive sampling, associative and associative methods). The analysis used is quantitative data analysis. Results Based on the partial test, it shows that the Current Ratio has an effect on Return On Assets, and the Debt To Asset Ratio has no effect on Return On Assets in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange in 2015-2019. Simultaneously Current Ratio, and Debt To Asset Ratio have an effect on Return On Assets in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange in 2015-2019. The percentage contribution of the influence of Current Ratio and Debt To Asset Ratio on Return On Assets is 45.5%, while the remaining 54.5% can be explained by other factors not examined in this study.